Long-term follow-up of hepatitis-associated aplastic anaemia - Gonçalves, Cristina (BMJ Case Rep, 2017)
Prognosis of hepatitis-associated aplastic anaemia (HAAA) was improved with haematopoietic stem cell transplantation (HSCT) and immunosuppression, but the long-term outcome remains undefined. Case 1: a girl aged 3 years with acute liver failure (ALF) submitted to orthotopic liver transplantation (OLT) subsequently developed aplastic anaemia and HSCT from a compatible sibling was performed. Post-HSCT, the patient developed post-transplant lymphoproliferative disorder and rituximab was administered with good response. Fifteen years later, both grafts show good outcome. Case 2: a girl aged 10 years submitted to OLT due to ALF, developed pancytopenia 2 months later. Due to the absence of a human leucocyte antigen compatible donor, she was treated with ciclosporin and antithymocyte globulin with very good long-term outcome. These clinical cases suggest that, for patients with HAAA that underwent OLT, aggressive therapy with HSCT or immunosuppression may provide a benign long-term outcome.